Seeing Suffering through the Perspective of the Already and the Not Yet from Paul the Apostle - Limasaputra, Alexander Darmawan (Veritas: Jurnal Teologi dan Pelayanan, 2018)
Suffering is something that is experienced by everyone. Suffering has made people cry out to God, question God or even leave God. Does suffering prove that God does not exist? Doesn’t God’s existence nullify suffering? Does suffering prove that God is impotent and no longer has power over the world? This article will address these questions through the framework of the already and the not yet schema developed by the apostle Paul. The author explains that suffering is a part of the call of believers because it is experienced between the time of the already and the not yet. A period when Jesus Christ has won over the power of sin, the curse of the universe and the government of Satan and is the time of God’s government in the world, even though all this has not yet reached fullness. Therefore, believers need not fear suffering nor leave the Christian faith because of it.